Rhophilin rho GTPase binding protein 1-antisense RNA 1 (RHPN1-AS1) promotes ovarian carcinogenesis by sponging microRNA-485-5p and releasing DNA topoisomerase II alpha (TOP2A). Issue 2 (20th December 2021) - Zhou, Yi; Li, Jing; Yang, Xiaoxin; Song, Yu; Li, Haigang
ABSTRACT: Ovarian cancer (OC) is the most common and lethal gynecological cancer worldwide. Long non-coding RNAs (lncRNAs) and sponging microRNAs (miRNAs) serve as key regulators in the biological processes of OC. We sought to evaluate the effect of the RHPN1-AS1-miR-485-5p-DNA topoisomerase II alpha (TOP2A) axis in regulating OC progression. RHPN1-AS1, miR-485-5p, and TOP2A levels in OC tissues and cells were determined by RT-qPCR. The interaction of RHPN1-AS1/miR-485-5p/TOP2A was assessed using luciferase, RNA immunoprecipitation, and RNA pull-down assays. RHPN1-AS1 silencing allowed us to explore its biological function by measuring cell viability, proliferation, migration, invasion, and apoptosis in OC cells. In vivo experiments were performed to verify the in vitro findings. We found that the RHPN1-AS1 and TOP2A levels were significantly enhanced, whereas the miR-485-5p levels were reduced in OC tissues and cells. RHPN1-AS1 silencing attenuated cell growth, facilitated apoptosis in OC cells, and inhibited tumor growth in vivo . Notably, RHPN1-AS1 negatively regulating miR-485-5p promoted the TOP2A expression in OC cells. In conclusion, RHPN1-AS1 sponging miR-485-5p accelerated the progression of OC by elevating TOP2A expression, which makes it a promising target for the treatment of OC patients.